Underreporting of work accidents associated with blood-borne risk factors - Vieira, Cláudia; Góis, Joaquim; Laranjeira, Paulo; Pinho, Paulo; Norton, Pedro (La Medicina del Lavoro, 2022)
Background: Work accidents (WA) due to percutaneous or mucocutaneous injury are extremely frequent among health professionals. The notification of these accidents ensures not only the compliance with legal requirements, but it also enables health institutions to develop, implement and evaluate strategies to prevent them. This study aimed to estimate the proportion of underreporting of work accidents caused by percutaneous and mucocutaneous lesions in a hospital setting, as well as its determinants. Methods: A self-administered questionnaire was made available to all hospital employees. Age, gender, professional category and type of service adjusted odds ratios (OR) and 95% confidence intervals (95%CI) were computed by multivariate logistic regression models. Results: Underreporting of WA associated with biological risk factors was high, particularly in accidents by mucocutaneous injury (80.9%). Physicians were the professional category that least reported this type of work accidents (OR=4.64; 95%CI 2.20-9.78). The main determinants of underreporting were the underestimation of the risk of transmission and the excessive bureaucracy. Conclusions: The underreporting of work accidents associated with biological risk factors was considerable and it contributes to a high degree of uncertainty on accidents’ characterization.